2022
DOI: 10.1051/0004-6361/202142805
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the stellar content of SDSS EELGs through self-consistent spectral modelling

Abstract: Extreme emission line galaxies (EELGs) are a notable galaxy genus, ultimately being regarded as local prototypes of early galaxies at the cosmic noon. Robust characterisation of their stellar content, however, is hindered by the exceptionally high nebular emission present in their optical spectroscopic data. This study is dedicated into recovering the stellar properties of a sample of 414 EELGs as observed by the SDSS Survey. Such is achieved by means of the spectral synthesis code FADO, which self-consistentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 67 publications
1
13
1
Order By: Relevance
“…In this way, the apparent disagreement of the results from Breda et al (2022) with the results reported here and in Cardoso et al (2022) is probably related to the level of the nebular continuum contribution of the galaxies that is included in the sample used in each of these works. In our sample, the median value of the Hα EW is 34 Å and only 6% of the galaxies in the sample have an EW(Hα)>100 Å (in Figure 3 is presented the EW(Hα) distribution).…”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…In this way, the apparent disagreement of the results from Breda et al (2022) with the results reported here and in Cardoso et al (2022) is probably related to the level of the nebular continuum contribution of the galaxies that is included in the sample used in each of these works. In our sample, the median value of the Hα EW is 34 Å and only 6% of the galaxies in the sample have an EW(Hα)>100 Å (in Figure 3 is presented the EW(Hα) distribution).…”
Section: Discussionmentioning
confidence: 50%
“…The estimate of comparable stellar masses by FADO relative to a purely stellar approach to SED fitting was also observed in Cardoso et al (2022). However, Breda et al (2022) observed that not considering the nebular contribution leads to an overestimation of the stellar mass.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations